Ultra-high-frequency ECG volumetric and negative derivative epicardial ventricular electrical activation pattern - Leinveber, Pavel; Halamek, Josef; Curila, Karol; Prinzen, Frits; Lipoldova, Jolana; Matejkova, Magdalena; Smisek, Radovan; Plesinger, Filip; Nagy, Andrej; Novak, Miroslav; Viscor, Ivo; Vondra, Vlastimil; et al. (Scientific reports, 2024)
From precordial ECG leads, the conventional determination of the negative derivative of the QRS complex (ND-ECG) assesses epicardial activation. Recently we showed that ultra-high-frequency electrocardiography (UHF-ECG) determines the activation of a larger volume of the ventricular wall. We aimed to combine these two methods to investigate the potential of volumetric and epicardial ventricular activation assessment and thereby determine the transmural activation sequence. We retrospectively analyzed 390 ECG records divided into three groups-healthy subjects with normal ECG, left bundle branch block (LBBB), and right bundle branch block (RBBB) patients. Then we created UHF-ECG and ND-ECG-derived depolarization maps and computed interventricular electrical dyssynchrony. Characteristic spatio-temporal differences were found between the volumetric UHF-ECG activation patterns and epicardial ND-ECG in the Normal, LBBB, and RBBB groups, despite the overall high correlations between both methods. Interventricular electrical dyssynchrony values assessed by the ND-ECG were consistently larger than values computed by the UHF-ECG method. Noninvasively obtained UHF-ECG and ND-ECG analyses describe different ventricular dyssynchrony and the general course of ventricular depolarization. Combining both methods based on standard 12-lead ECG electrode positions allows for a more detailed analysis of volumetric and epicardial ventricular electrical activation, including the assessment of the depolarization wave direction propagation in ventricles.
Keywords: Arrhythmias, Cardiac; elektrokardiografie; Bundle-Branch Block; blokáda Tawarova raménka; Electrocardiography; retrospektivní studie; lidé; Heart Ventricles; Retrospective Studies; srdeční arytmie; srdeční komory; Humans